Relationship between online compulsive shopping and impulsivity in females - Namlı, Zeynep; Tamam, Lut; Demirkol, Mehmet Emin; Karaytuğ, Mahmut Onur; Özbay, Aynur (Journal of Dependence, 2022)
Objective: Traditional shopping methods have been replaced by online shopping recently. There is limited research on online compulsive shopping, characterized as impulse control disorder or behavioral addiction. Our study aimed to investigate the relationship between online shopping behavior, sociodemographic characteristics, and impulsivity in women. Methods: We included 132 women who were not diagnosed with mental disorders due to the psychiatric interview. A sociodemographic data form, Compulsive Online Shopping Scale (COSS), Wender-Utah Rating Scale (WURS), and UPPS Impulsive Behavior Scale, were administered to the participants. Results: 77 (58.3%) participants had online shopping behavior. The education level of the group with online shopping behavior was significantly higher than the group without the behavior. WURS and UPPS sensation-seeking subscale mean scores were significantly higher in the group with online shopping behavior than in the group without (20.7 ± 15.7 & 15.4 ± 13.0, 23.9 ± 8.7 & 20.3 ± 9.4, respectively). There was no significant correlation between the COSS scores and the WURS and UPPS Impulsive Behavior Scale subscale scores of participants with online shopping behavior. Conclusion: These findings suggest that online shopping behavior in women is related to personality traits such as impulsivity rather than sociodemographic characteristics. Future studies evaluating other personality traits in a large sample may contribute to the diagnostic classification of compulsive shopping.